MODEL SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 17 PIDIE - Zahrina; Rahmah Rusli (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
The purpose of this study was to determine whether the application of the Scramble model can improve the learning outcomes of 4th grade students of MIN 17 Pidie. The type of research carried out was Classroom Action Research (CAR) with 23 of 4th grade students of MIN 17 Pidie as research subjects. The data collection techniques used were observation, tests, and interviews. From the results of the study, it was known that in cycle I, the average value obtained by students was 59.56 and the classical completeness achieved by students was 34.79%. In cycle II, the average value obtained by students was 77.39 and the classical completeness achieved by students was 65.20%. In cycle III, the average value obtained by students was 93.04 and the classical completeness obtained by students was 100%. Thus, it can be concluded that the application of the Scramble model can improve the learning outcomes of 4th grade students of MIN 17 Pidie.